Docência Universitária: o professor agrônomo na construção de sua professoralidade - Kato, Marly Nunes de Castro (2015)
The aim of this study was to understand how does the teaching learning process of the agronomy professor from Universidade Federal de Uberlândia occurs, analyzing the relationship among training, knowledge and these professors professional identity. The questions which guided the research were: How does the professional identity of these professors are developed in the teaching learning process? Which are the main formation factors that influences this process? Which are the agronomy professors knowledge and how were them built and learned by these professionals in college? This is a research with a qualitative approach, in which most of the data was collected with the professors, through two questionnaires, a simplified and an in-depth one, as well as documents that depict the history of the institute and of the Agronomy department. To guide analysis, we have used, more than the scientific production in the area, the authors Cunha (2008), Tardif (2002), Pimenta (2005), Melo (2009, 2012), Malusá (2005), Pachane (2009), Magalhães (2012), Dubar (2005), Imbernón (2002),Nunez andRamalho (2008), Almeida andPimenta (2012) PimentaandAnastasiou (2002), Cavallet (1999) Pachane (2006), Behrens (2007) Isaia (2008), Malusá (2012) and Nóvoa (1999). The analysis indicated that the teaching learning process of the agronomy professor occurs since college, with the option of been a professor, and throughout their teaching career. Their challenges are related to work conditions, although, the dilemmas between the practices related to the conceptions of traditional and progressive pedagogy can be seen in their class, teaching and teaching learning process conception. Classes are considered by professors as an interaction place but also as a knowledge transference place. This research identifies the necessity of promote cooperation between teachers, so that, the collective and integrated work in formative spaces teachers will have the opportunity to develop the knowledge necessary for teaching. The implementation of institutional initial and continuous formation, through direct dialogue between undergraduate, graduate and training and professional development programs for teachers, with better work conditions will reflect in the constant improvement of training development within universities.